Infrastructure Analysis on Technology in PT Sinar Sosro Products - Sari Yuliani; Hilda Septiani; Hari Matahari; Fenny Purwani (Bahasa Indonesia, 2023)
This article delves into the ways in which PT. Sinar Sosro utilizes product information system technology. One such business is PT Sinar Sosro, which specializes in tea-based soft beverages. When it comes to ready-to-drink tea in bottles, PT Sinar Sosro was an early pioneer in both Indonesia and the global market. This company produces a bottled tea drink called the Botol Sosro. Sosro bottled tea only uses original and natural ingredients. The tea leaves are picked from the plantation itself. Then, it is produced into fragrant tea, namely green tea mixed with jasmine flowers and gambier flowers. So that it produces a unique taste, its distinctiveness is always maintained, and its quality is guaranteed. The tea plantations that provide PT. Sinar Sosro with their raw materials are located in many parts of Indonesia, including the Cianjur, Galrut, Mount Rosa, Mount Manik, Mount Cempaka, Neglasari region, Cukul area, Pangelengan, and Sambawa areas. A number of PT Sinar Sosro's plants are located all across Indonesia. As it has grown, PT Sinar Sosro has expanded its product distribution throughout the archipelago via its network of sales branch offices. Beyond its home market, PT Sinar Sosro has expanded into international trade by supplying non-glass bottles and other one-way packaging items to various nations throughout the globe.